Thyroid Hormone Levels And Cardiometabolic Risk Factors In Hypertensive Adult Ghanaians - Nkrumah, Christopher (2014)
A thesis submitted to the Department of Clinical Microbiology, School of Medical Sciences, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the degree of Master of Philosophy, May-2011